DOES ECONOMIC GROWTH HAS AN IMPACT ON EAST JAVA REGIONAL REVENUE? - Faishal Fadli (Quantitative Economics Journal, 2016)
The implementation of regional autonomy resulted in each region to be able to manage their finances independently. This is one way the central government toremove the dependency of local governments to the central government. Thusrequiring local governments to explore the sources of local revenue in order tofinance regional development. In an effort to increase local revenues derived from the PAD is determined by economic factors or economic potential which has the prospect to be developed for each area. The result indicates the role of the revenue (PAD) in the Regional Budget (APBD) of East Java Province indicates that there is still very small, with an average of 15.47% of the total revenue budget. This means that the level of dependence of local governments on the central government is still high. Although the results of regional revenue projections indicate that component has been great in their contribution of the reception area, which amounted to 69.52%. Using the ordinary least squre method, the result of regression correlation are insignificant. This means that the regional gross domestic product does not have an effect on revenue of East Java Province.